Deracemization By Simultaneous Bio‐oxidative Kinetic Resolution and Stereoinversion1. Issue 14 (24th February 2014) - Schrittwieser, Joerg H.; Groenendaal, Bas; Resch, Verena; Ghislieri, Diego; Wallner, Silvia; Fischereder, Eva‐Maria; Fuchs, Elisabeth; Grischek, Barbara; Sattler, Johann H.; Macheroux, Peter; Turner, Nicholas J.; Kroutil, Wolfgang
Abstract Deracemization, that is, the transformation of a racemate into a single product enantiomer with theoretically 100 % conversion and 100 % ee, is an appealing but also challenging option for asymmetric synthesis. Herein a novel chemo‐enzymatic deracemization concept by a cascade is described: the pathway involves two enantioselective oxidation steps and one non‐stereoselective reduction step, enabling stereoinversion and a simultaneous kinetic resolution. The concept was exemplified for the transformation of rac‐benzylisoquinolines to optically pure (S)‐berbines. The racemic substrates were transformed to optically pure products (ee>97 %) with up to 98 % conversion and up to 88 % yield of isolated product.